INITIAL EXPERIENCE WITH TOTALLY LAPAROSCOPIC VAGINOPLASTY USING SIGMOID COLON AT VIET DUC UNIVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To present our initial experience with total laparoscopic Sigmoid vaginoplasty combined with clitoroplasty and urethral reconstruction in a single-stage procedure.Subjects and methods: A retrospective descriptive study was conducted on one patient who underwent total laparoscopic Sigmoid vaginoplasty at Viet Duc University Hospital.Results: A 25-year-old female patient with a 46, XX karyotype and congenital vaginal agenesis underwent total laparoscopic Sigmoid vaginoplasty. The procedure was performed through a combined abdominal and perineal approach. Hypertrophic clitoral tissue was resected, followed by clitoroplasty. Simultaneously, approximately 5 cm of the urethra was reconstructed using a clitoral mucosal skin flap in order to relocate the urethral meatus from the perineal region to a position adjacent to the clitoris. A 15-17 cm neovaginal conduit was created laparoscopically using a Sigmoid colon segment and exteriorized through the perineum. Intestinal continuity was restored using a circular stapling device. No intraoperative complications occurred. Estimated blood loss was approximately 500 mL. Operative time was 7 hours. Postoperative hospital stay was 21 days. Vaginal dilation was initiated on postoperative day 1.Conclusion: Our initial experience suggests that Sigmoid vaginoplasty combined with simultaneous clitoroplasty and urethral reconstruction in a single-stage procedure is feasible and effective. The surgery requires a well-coordinated multidisciplinary surgical team.
Keywords: Total laparoscopic Sigmoid vaginoplasty, clitoroplasty, urethral reconstruction.